Effectiveness Of Dakon Media In Improving Numeracy Skills In Lower Grade Elementary School Students - Pinasti Pinahayu; Ahmad Singgih Prayogo (Prosiding University Research Colloquium, 2021)
The purpose of this study is to determine the effectiveness of the use of dakon mediain improving numeracy skills in lower grade elementary school students. Thisresearch uses pre-experimental research method with one group pretest and posttestresearch design design. The subjects of this study were as many as 10 grade 1elementary school students consisting of various schools. The research is divided intotwo cycles, namely before and after being given special treatment. The mean testresult before treatment is 41 and the posttest test result gets 79 which results inthe mean difference between pretest and posttest which is 38. Where there is amean increase from the pretestt to the posttest. From the results of the studystudents showed an increase of pretest which only showed that as many as 90% ofstudents were incomplete and only 10% of students completed. The studentlearning results in the posttest test showed an increase of 20% of students wereincomplete and 80% of students completed.